Middle Atmospheric Water vapor vertical Profiles at the Thule High Arctic Atmospheric Observatory (THAAO_MAWP) - Muscari, Giovanni; Mevi, Gabriele; Di Sarra, Alcide; Di Iorio, Tatiana; Meloni, Daniela; Pace, Giandomenico; Iaccarino, Antonio; Calì Quaglia, Filippo; Sensale, Gianpaolo (2018)
Middle Atmospheric Water vapor vertical Profiles at the Thule High Arctic Atmospheric Observatory (THAAO_MAWP)